An Analysis of Structure, Fire and Social Vulnerabilities of Chittagong City Corporation Area due to Earthquake Hazard (Journal of Bangladesh Institute of Planners, 2017)
Chittagong city is the second largest city of Bangladesh. Due to rapid rate of urbanization and unplanned growth of urban centers, disasters like earthquake have become a menace for Chittagong. Most of the structures are owner built, non-engineered in nature and structurally vulnerable for earthquake. Ward no 29 (South Agrabad) which acts as CBD of Chittagong was selected for earthquake vulnerability assessment. A total of 86 buildings were selected by Simple random sampling procedure keeping the confidence level at 90%. Structure vulnerability assessment has been analyzed by a FEMA-RVS method, fire hazards vulnerability assessment has been done with the help of method developed by ADPC (2004) and social vulnerability assessment was done with the help of method developed by World Bank (2014). Finally, structure, fire and social vulnerabilities were integrated by composite vulnerability score developed by Rahman et al. (2015). From the analysis, it has been found that most of the structures are very highly vulnerable to earthquake and fire hazard and low social impacts are observed against earthquake. The findings of the research can be used to prioritize risk mitigation investments, measures to strengthen the emergency preparedness and response mechanisms for reducing the losses and damages due to future earthquake events.JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 89-104